The Effect of Problem Based Learning Methods and Self Confidence to English Learning Outcomes in the Elementary School Students - Sita Ratnaningsih; Desi Nahartini; Atik Yuliyani (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2018)
AbstractFrom Central Statistics Agency, the total number of primary schools in Indonesia are 147,536 which most of them have not got any good learning outcomes especially in English. This study aims to determine the effect of Problem Based Learning method and students' self-confidence in English learning outcomes. This research was conducted on the fourth grade students of Al-Fath Primary School, South Tangerang Indonesia, with the number of students as many as 4 classes consisting of 96 students, from the population of 120 students. The method used in this research is the experimental method with the design of treatment design by level 2 x 2. The results showed that: 1) English learning result between students who taught using Problem Based Learning method is higher than Expository method, 2) There is interaction effect between Problem Based Learning method with students' self confidence, 3) For students who have high confidence, English learning outcomes taught using the Problem Based Learning method is higher than taught using the Expository method, 4) For students a low level of confidence, English learning outcomes of students taught using the Problem Based Learning method is lower than the Expository method.AbstrakDari data Badan Pusat Statistik, jumlah sekolah dasar di Indonesia adalah 147.536, sebagian besar sekolah tersebut belum mendapatkan hasil pembelajaran yang baik terutama dalam bahasa Inggris. Penelitian ini bertujuan untuk mengetahui pengaruh metode Problem Based Learning dan kepercayaan diri siswa terhadap hasil belajar bahasa Inggris. Penelitian ini dilakukan pada siswa kelas IV Sekolah Dasar Al-Fath, Tangerang Selatan, dengan jumlah siswa sebanyak 4 kelas yang terdiri dari 96 siswa, dari populasi 120 siswa. Metode yang digunakan dalam penelitian ini adalah metode eksperimental dengan perancangan desain faktorial level 2 x 2. Hasil penelitian menunjukkan bahwa: 1) Hasil belajar bahasa Inggris siswa yang diajar menggunakan metode Problem Based Learning lebih tinggi daripada yang diajar menggunakan metode Ekspositori, 2) Ada pengaruh interaksi antara metode Problem Based Learning dengan kepercayaan diri siswa, 3) Bagi siswa yang memiliki kepercayaan diri tinggi, hasil belajar bahasa Inggris yang diajar menggunakan metode Problem Based Learning lebih tinggi daripada menggunakan metode metode Ekspositori, 4) Bagi siswa yang memiliki tingkat kepercayaan yang rendah, hasil pembelajaran bahasa Inggris yang diajar menggunakan metode Problem Based Learning hasilnya lebih rendah daripada yang menggunakan metode pembelajaran Ekspositori. How to Cite : Ratnaningsih, S., Nahartini, D., Yuliyani, A. (2018). The Effect of Problem Based Learning Methods and Self Confidence to English Learning Outcomes in the Elementary School. TARBIYA: Journal of Education in Muslim Society, 5(2), 135-144. doi:10.15408/tjems.v5i2.10640.